Exploration and exploitation in established small and medium-sized enterprises: The effect of CEOs' regulatory focus - Kammerlander, Nadine; Burger, Dominik; Fust, Alexander; Fueglistaller, Urs (Journal of Business Venturing, 2015)
Based on theory of regulatory focus and organizational ambidexterity, we hypothesize that the level of engagement in exploration and exploitation in a small or medium-sized enterprise (SME) is affected by the respective CEO's chronic regulatory focus. In our analysis of survey responses from CEOs in Switzerland, we find that the CEO's level of promotion focus positively affects the firm's engagement in both, exploration and exploitation, while the CEO's prevention focus is negatively associated with the firm's exploration but not significantly related to its exploitation. The positive associations between a CEO's promotion focus and the firm's exploration/exploitation activities are enhanced under conditions of intense competition.